Elder abuse and neglect in nursing homes as a reciprocal process: the view from the perspective of care workers. Issue 1 (19th November 2021) - Gil, Ana Paula; Capelas, Manuel Luis
Abstract : Purpose: Reciprocal abuse inside care practices remain under-studied due to their invisibility and further research is required. The purpose of this paper is to explore different levels of conflicts inside organisations. Design/methodology/approach: The paper is based on a self-administered questionnaire filled out by care workers (n = 150), in 16 Portuguese care homes. Findings: Results indicated that, overall, 54.7% of care workers had observed abuse, in their daily practice, in the preceding 12 months: 48.7% psychological; 36.0% neglectful care practices; 14.0% physical and 3.3% financial abuse. The figures decreased significantly as regards abuse committed themselves, with 16.7% of those admitting to having committed at least one of these behaviours. The highest figures were also recorded for psychological abuse (13.3%) and neglect (6.7%). However, there is a statistically significant relationship between abuse committed by care workers and abuse committed by residents. Overall, 52.0% of care workers reported having been the target of at least one such behaviour by residents. Research limitations/implications: This paper has its limitations as the sample consisted of only 16 nursing homes (12 not-for-profit and 4 for-profit nursing homes). The fact that only 4 of the 16 LTC homes were for-profit is a potential limitation both in general and in particular because research has shown that lower quality of care and elder abuse and neglect are more common in for-profit nursing homes at least in Portugal. The results were also based on self-reported measures. Practical implications: A reactive behaviour, the risk of retaliation, after a complaint, the difficulty in dealing with dementia and the residents' aggressive behaviour, an absence of a training and support policy in an environment where difficult working conditions prevail, are factors enhancing a reciprocal process of abuse. The analysis followed by a discussion of potential implications to prevent institutional elder abuse and neglect, based on communication and social recognition, including better working conditions and training, and a cooperative work environment. Social implications: Conflict is much more than reducing an interpersonal relationship problem between residents and staff (care workers, professional staff, managers) and extending to the whole organisation. Therefore, there are still uncertainties on how organisations, staff and residents interact between themselves, and affect care practises. Originality/value: Reciprocal abuse in nursing homes is an important area of research and this paper enabled a discussion of potential implications concerning the quality of care, which required the identification of levels of conflict, in an organisational system, including interactions, the context where care is provided, difficult working conditions, lack of training and levels of support. All these factors are important when considering elder abuse and neglect and this calls for special attention by policymakers and researchers.